PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN CABRI 3D UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI JARAK DALAM RUANG DIMENSI TIGA SISWA KELAS XII MAN 2 KOTA PALU - Badjeber, Kamila; Rizal, Muh.; Bennu, Sudarman (Universitas Tadulako, 2023)
This study aims to obtain a description of the application of the STAD type cooperative learning model assisted by Cabri 3D software to improve learning outcomes on distance material in the three-dimensional space of class XII Man 2 students in Palu City. The subjects of this study were students of class XII IPA 7 MAN 2 Palu City, totaling 25 people. This research is a Class Action Research that follows the research design of Kemmis and Mc. Taggart, namely (1) planning, (2) implementation of actions and observations, (3) reflection. The study was conducted in two cycles. The application of the STAD type cooperative learning model assisted by Cabri 3D software that can improve learning outcomes on distance material in the three-dimensional space of class XII MAN 2 students in Palu City follows the phases, namely: 1) Conveying learning objectives and motivating students, teachers conveying learning objectives, motivating students and providing apperceptions, 2) Presenting material, the teacher presents the material in a creative way using powerpoint and 3D Cabri, 3) Organizing students into cooperative groups, students joining their respective groups and the teacher explaining the responsibilities of students in groups, 4) Guiding groups to work and study, students cooperate with each other and help their group friends, 5) Evaluation, students present the results of group answers and students respond to the results of the presentation, 6) Awarding Awards, teachers give awards to the whole group.